Impact of Back Massage on Anxiety Levels in Patients Undergoing Orthopedic Surgery - Jasmine Soundharya S. (International Journal of Orthopedic Nursing and Practices, 2024)
Objectives: The objective of the study was to assess the pre- and post-test levels of anxiety in patients who underwent orthopaedic surgery in both the experimental and control groups, to evaluate the effectiveness of back massage in reducing anxiety among patients in the experimental group, and to explore the association between anxiety levels and selected demographic variables in these patients. Research approach: The aim of the study was to evaluate how effective back massage is in reducing anxiety levels in patients who have undergone orthopaedic surgery. Given the nature of the problem and to achieve the objectives, a quantitative evaluative approach was employed. Findings: The chi-square value calculated for baseline variables indicated a significant association between the anxiety levels of patients who underwent orthopaedic surgery and their selected demographic characteristics, as the value exceeded the table value. Thus, hypothesis H2 is supported, indicating a link between these variables and the level of anxiety.
Keywords: Experimental and Control groups; back massage; level of anxiety; orthopaedic surgery; patients